14.8k views
4 votes
Please someone answer this please

Please someone answer this please-example-1
User Matt Ryall
by
5.1k points

1 Answer

5 votes

Option C:


(3 a^(2) b^(11))/(2 ) is equivalent to the given expression.

Solution:

Given expression:


$(-18 a^(-2) b^(5))/(-12 a^(-4) b^(-6))

To find which expression is equivalent to the given expression.


$(-18 a^(-2) b^(5))/(-12 a^(-4) b^(-6))

Using exponent rule:
(1)/(a^m)=a^(-m), \ \ (1)/(a^(-m))=a^(m)


$=(-18 a^(-2) b^(5)a^(4) b^(6))/(-12 )


$=(-18 a^(-2) a^(4) b^(5) b^(6))/(-12 )

Using exponent rule:
{a^m}\cdot{a^n}=a^(m+n)


$=(-18 a^((-2+4)) b^((5+6)))/(-12 )


$=(-18 a^(2) b^(11))/(-12 )

Divide both numerator and denominator by the common factor –6.


$=(3 a^(2) b^(11))/(2 )


$(-18 a^(-2) b^(5))/(-12 a^(-4) b^(-6))=(3 a^(2) b^(11))/(2 )

Therefore,
(3 a^(2) b^(11))/(2 ) is equivalent to the given expression.

Hence Option C is the correct answer.

User Muton
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.